The European challenges of funding orphan medicinal products - Szegedi, Márta; Zelei, Tamás; Arickx, Francis; Bucsics, Anna; Cohn-Zanchetta, Emanuelle; Fürst, Jurij; Kamusheva, Maria; Kawalec, Pawel; Petrova, Guenka; Slaby, Juraj; Stawowczyk, Ewa; Vocelka, Milan; et al. (Orphanet journal of rare diseases, 2018)
BACKGROUND: Funding of orphan medicinal products (OMPs) is an increasing challenge in the European Union (EU). OBJECTIVES: To identify the different methods for public funding of OMPs in order to map the availability for rare disease patients, as well as to compare the public expenditures on OMPs in 8 EU member states. METHODS: Information on the reimbursement status of 83 OMPs was collected in 8 countries by distinguishing standard and special reimbursements. In two consecutive years, the total public expenditures on OMPs were calculated by using annual EUR exchange rates. Annual total public expenditures were calculated per capita, and as a proportion of GDP, total public pharmaceutical and healthcare budgets. Differences between countries were compared by calculating the deviations from the average spending of countries. RESULTS: In 2015 29.4-92.8% of the 83 OMPs were available with any kind of public reimbursement in participant countries including special reimbursement on an individual basis. In Austria, Belgium and France more OMPs were accessible for patients with public reimbursement than in Bulgaria, Czech Republic, Hungary and Poland. Standard reimbursement through retail pharmacies and/or hospitals was applied from 0 to 41% of OMPs. The average annual total public expenditure ranged between 1.4-23.5 €/capita in 2013 and 2014. Higher income countries spent more OMPs in absolute terms. Participant countries spent 0.018-0.066% of their GDPs on funding OMPs. Average expenditures on OMPs were ranged between 2.25-6.51% of the public pharmaceutical budget, and 0.44-0.96% of public healthcare expenditures. CONCLUSIONS: Standard and special reimbursement techniques play different roles in participant countries. The number of accessible OMPs indicated an equity gap between Eastern and Western Europe. The spending on OMPs as a proportion of GDP, public pharmaceutical and healthcare expenditure was not higher in lower income countries, which indicates substantial differences in patient access to OMPs in favour of higher-income countries. Equity in access for patients with rare diseases is an important policy objective in each member state of the EU; however, equity in access should be harmonized at the European level.
Keywords: Evropská unie; náklady na léky; Drug Costs; Orphan Drug Production; výroba orphan drugs; Europe; European Union; Rare Diseases; Evropa; vzácné nemoci; Orphan medicinal products; Patient access; Funding; Humans; Equity; Health Expenditures; Reimbursement; výdaje na zdravotnictví; lidé